Between‐population differences in constitutive and infection‐induced gene expression in threespine stickleback. Issue 24 (18th October 2021) - Fuess, Lauren E.; Weber, Jesse N.; den Haan, Stijn; Steinel, Natalie C.; Shim, Kum Chuan; Bolnick, Daniel I.
Abstract: Vertebrate immunity is a complex system consisting of a mix of constitutive and inducible defences. Furthermore, host immunity is subject to selective pressure from a range of parasites and pathogens which can produce variation in these defences across populations. As populations evolve immune responses to parasites, they may adapt via a combination of (1) constitutive differences, (2) shared inducible responses, or (3) divergent inducible responses. Here, we leverage a powerful natural host‐parasite model system ( Gasterosteus aculeatus and Schistochephalus solidus ) to tease apart the relative contributions of these three types of adaptations to among‐population divergence in response to parasites. Gene expression analyses revealed limited evidence of significant divergence in constitutive expression of immune defence, and strong signatures of conserved inducible responses to the parasite. Furthermore, our results highlight a handful of immune‐related genes which show divergent inducible responses which may contribute disproportionately to functional differences in infection success or failure. In addition to investigating variation in evolutionary adaptation to parasite selection, we also leverage this unique data set to improve understanding of cellular mechanisms underlying a putative resistance phenotype (fibrosis). Combined, our results provide a case study in evolutionary immunology showing that a very small number of genes may contribute to genotype differences in infection response.